Targeting Americans : the constitutionality of the U.S. drone war - Powell, Jefferson, 1954- (New York, NY : Oxford University Press, 2016)
A centerpiece of the U.S. government's current war against international terrorism is targeted killing by unmanned drone aircraft. The executive branch insists that it limits the use of drone strikes to conform with all relevant legal norms but also that those norms permit the killing of a U.S. citizen who meets the targeting criteria: The killing of Anwar al-Awlaki in September 2011 was the first acknowledged strike against a citizen. The legality as well as the wisdom of the government's policies are hotly debated, and this book analyzes the constitutionality of the killing of al-Awlaki as a lens for examining the lawfulness of the drone strike policies in general.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 18, 2016).
Keywords: War and emergency powers -- United States; Targeted killing -- United States; Constitutional law -- United States; National security -- Law and legislation -- United States; State crimes -- Law and legislation -- United States; Drone aircraft -- Law and legislation -- United States; Targeted killing -- Moral and ethical aspects; Counterinsurgency -- United States; Law